Maximizing After Sales Service and Service Recovery to Increase Customer Satisfaction : Literature Review of Industrial Control System customers in Indonesia - Gaffar, Ichsan; Hajar, Elvira Sitna; Aisha, Neila (Ilomata International Journal of Management, 2026)
After-sales service (ASS) and service recovery (SR) are increasingly recognized as critical elements in sustaining customer satisfaction and supplier credibility. While prior studies have examined these concepts across consumer and manufacturing sectors, their specific role in Industrial Control Systems (ICS) remains underexplored, particularly within the Indonesian context. ICS represents a high-value, capital-intensive asset that requires continuous operation and long-term supplier support, making after-sales activities a strategic necessity. This study aims to analyze the extent to which ASS and SR contribute to strengthening customer satisfaction and safeguarding supplier reputation in the ICS sector. Unlike earlier research that largely repackages established concepts, this paper critically frames the unique challenges of ICS such as warranty limitations, post-warranty risks, and the vulnerability of installed bases to highlight gaps in both theory and practice. The methodology employed is a structured literature review, drawing from peer-reviewed journals indexed in Scopus, Google Scholar, and Semantic Scholar, complemented with ICS technical references and supplier documentation. From this synthesis, the paper develops a conceptual framework positioning ASS and SR as antecedents of customer satisfaction, which subsequently reinforces supplier reputation and long-term loyalty in capital-intensive industries. The study concludes that effective ASS and SR are not only operational requirements but also strategic levers that determine competitiveness. By contextualizing these concepts within ICS in Indonesia, the research contributes a more critical perspective and offers both theoretical insights and practical implications for sustaining supplier–customer relationships.